The efficacy of a novel porcine-derived collagen membrane on guided bone regeneration: a comparative study in canine model - Anh Thi Mai Nguyen; Euphemie Landao-Bassonga; Elias D. Kontogiorgos; Clair Lee; Tak Cheng; Hien Chi Ngo; Brent Allan; Mithran Goonewardene; Lynne A. Opperman; Minghao Zheng (BMC Oral Health)
Abstract Background This study aimed to evaluate the performance of the novel Striate + collagen membrane in a canine model of guided bone and tissue regeneration (GBR) with dental implant placement. Methods Eighteen mature beagle dogs were used in this split-mouth study. After having their premolar teeth extracted, GBR with immediate implant placement was performed on all study subjects. study subjects. The study treatments were: control group (implant + no membrane); BG-group (implant + Bio-Gide membrane); and SG-group (implant + Striate + membrane). Six dogs were sacrificed at 4-, 8- and, 12-weeks post-treatment for radiographic (µCT) assessment, histological examination and histomorphometric analysis. Results µCT assessment showed that all groups exhibited increased bone formation from 4-weeks to 12-weeks post-treatment. There was no statistically significant difference in mean BV/TV between all 3 groups at weeks 4 and 8. At week 12, BV/TV was significantly higher in SG and BG-groups compared to control group. Assessment of bone microarchitectural parameters showed that animals in SG-group exhibited significantly higher Tb.N, O.Wi and lower Tb.Sp, suggesting more favorable mature bone structure. A significant increase in the number of osteoblasts on bone surface was also seen in SG-group. Histological assessment showed that SG-group displayed early signs of bone-to-implant contact at 8 weeks. While control sites showed early ingrowth of epithelium and connective tissue into the defects, infiltration of inflammatory cells, incomplete bone formation and limited bone to implant contact, use of a barrier membrane resulted in significant bone infill, mature bone formation with good bone to implant contact. and limited soft tissue invasion. Conclusion This study demonstrated superiority of Striate + collagen membrane to promote good bone formation and prevent unwanted epithelial infiltration in a canine mode of GBR.